ANALISIS PENGARUH WORK FAMILY CONFLICT DAN FAMILY WORK CONFLICT TERHADAP TURNOVER INTENTION DENGAN JOB STREES SEBAGAI MEDIASI (STUDI PADA KARYAWAN WANITA CV. TIGA MUTIARA) - Sulis Riptiono (Management Insight: Jurnal Ilmiah Manajemen, 2017)
The purpose of this study is to analyze the influence of the influence of Work-Family Conflict and Family-Work Conflict on Employee Intention Turnover at CV. Tiga Mutiara in Kebumen City with Job Stress as Mediation Variable. Respondents in this research are employees of CV. Tiga MutiaraKebumen with 32 employees. The research method is quantitative analysis by using path analysis, the result of multiple regression analysis calculation is tested by t test and F test and coefficient of determination. The results of this study indicate that the variables Work-Family Conflict, Family-Work Conflict and Job Stress on turnover Intention have a positive effect on employees CV. Tiga Mutiara Kebumen. In this study it is known that Work-Family Conflict is the independent variable that has the greatest influence on Employee Turnover Intention compared to other independent variables.Keywords: Work-Family Conflict, Family-Work Conflict, Job Stress, Turnover Intention